Transformative Effect of Community Managed Nature Tourism on the Individual Wellbeing of Service Providers: An Empirical Study of Odisha, India - RAJDEEP DEB; Jagadish Behera; Jagadish Behera (Revista de turism - studii și cercetări în turism, 2025)
The current study delves into the impacts of community managed nature tourism (CMNT) on the individual wellbeing of service providers engaged with it. This study draws mainly from social exchange theory and was carried out in the developing state of Odisha, India. The empirical data were gathered using a questionnaire survey method from the service providers of eight nature camps in Odisha. A total of 141 responses were used for statistical analysis. To analyse the data, exploratory factor analysis along with regression analysis were used. The findings of the study reveal that CMNT has a positive and significant affect on the overall individual wellbeing (financial wellbeing, purpose of life and subjective wellbeing, and community attachment and satisfaction) of the service providers engaged with it in the context of study area. In a developing country like India and state like Odisha, to alleviate the extreme levels of poverty especially in remote areas, CMNT can evolve as an effective tool in the long run. Also, the current study offers useful insights to policymakers, administrators, and government about the effectiveness of CMNT in improving the wellbeing of the local people.